2013
DOI: 10.1017/s0022215112003283
|View full text |Cite
|
Sign up to set email alerts
|

Role of spirometry in detection of nasal obstruction

Abstract: Portable spirometry is an objective and useful method of evaluating nasal obstruction, but needs more investigation to establish a standardised test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Previous research indicated chronic tonsillitis to be one of the most common risk factors for OME, which is consistent with our findings. [21][22][23] The tympanogram results after six months of healed myringotomy were significantly improved in group III compared to group I compared to group II, as evidenced by the fact that there were 40 cases (80%) with type A tympanogram in group III compared to 13 cases (26% in group I) and 9 cases (18% in group II), Farhadi et al 26 reported that adenoidectomy plus tympanostomy tubes improved the tympanogram significantly, which was similar to our findings. Also, Shishegar and Hobhoghi 27 and Vlastos et al 28 found that adenoidectomy plus tympanostomy tube application improved tympanogram and Pure Tone Audiometry (PTA) in children with OME.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous research indicated chronic tonsillitis to be one of the most common risk factors for OME, which is consistent with our findings. [21][22][23] The tympanogram results after six months of healed myringotomy were significantly improved in group III compared to group I compared to group II, as evidenced by the fact that there were 40 cases (80%) with type A tympanogram in group III compared to 13 cases (26% in group I) and 9 cases (18% in group II), Farhadi et al 26 reported that adenoidectomy plus tympanostomy tubes improved the tympanogram significantly, which was similar to our findings. Also, Shishegar and Hobhoghi 27 and Vlastos et al 28 found that adenoidectomy plus tympanostomy tube application improved tympanogram and Pure Tone Audiometry (PTA) in children with OME.…”
Section: Discussionsupporting
confidence: 90%
“…Popova et al 34 discovered that the risk of relapse of OME was greater in the adenoidectomy with myringotomy group than the adenoidectomy with tympanostomy tube group. Furthermore, Farhadi et al 26 proposed that adenoidectomy is an effective surgical treatment in the management of otitis media, especially when combined with the insertion of TTs, which significantly reduces tube extrusion rate, possibly due to improved Eustachian tube function, which reduces repeated otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven articles excluded by full‐text review, four were observational studies 18–21 . The three remaining articles were RCTs but did not fulfill our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven articles excluded by full-text review, four were observational studies. [18][19][20][21] The three remaining articles were RCTs but did not fulfill our inclusion criteria. One assessed the influence of spirometry in general practice on the success rate of smoking cessation in adults 22 (excluded as incorrect population).…”
Section: Description Of Studiesmentioning
confidence: 99%